Effect of Ultrasonic Rolling on Surface Properties of GCr15 Spherical Joint Bearing - Hao Zhang; Xiuli Yang; Xiqiang Ma; Dongliang Jin; Jinyuan You (Lubricants, 2024)
Ultrasonic surface rolling process (USRP) has the potential to improve the surface mechanical properties of metal components with platelike or cylindrical macrostructure, but its effect on spherical surfaces remains to be studied in depth. In order to investigate the effect of USRP on the surface roughness, hardness and wear resistance of a spherical joint bearing made of GCr15 bearing steel, ultrasonic rolling strengthening was carried out on a spherical bearing surface under various conditions. The surface roughness and hardness variations of samples before and after strengthening were investigated. It was found that the USRP strengthening process can effectively enhance the surface properties of GCr15 spherical bearing materials, reduce the surface roughness by more than 45%, and increase the surface hardness by more than 10%. Friction and wear tests were carried out before and after ultrasonic rolling. The results show that the friction coefficient of the bearing surface can be reduced by 28%, and that the wear volume can be reduced by 29%. The variation in the friction coefficient correlated to the variance of wear volume as the reinforcement changes.